PENGARUH PEMBERIAN REBUSAN BATANG BAJAKAH (SPATHHOLOBUS LITTORALIS HASSK) TERHADAP PENAMPILAN REPRODUKSI MENCIT (MUS MUSCULUS) - Oktopiani, Oktopiani; Susanto, Bela Novita Amaris; Sari, Rina Puspita (Nusantara Hasana Berdikari, 2022)
Reproduction is the most important part of the life cycle. Many new cases of infertility caused by exposure to cigarette smoke. Pregnant women who are exposed to cigarette smoke can damage reproductive organs, such as the cervix, ovaries and fallopian tubes. The use of herbal plants can be a solution in the treatment of infertility. One of the plants that might be used is bajakah tampala, which contains flavonoids, tannins and saponins.